Cytotoxicity patterns of arsenic trioxide exposure on HaCaT keratinocytes - Udensi UK; Graham-Evans BE; Rogers CS; Isokpehi RD (Dove Medical Press, 2011)
Udensi K Udensi1,2, Barbara E Graham-Evans1, Christian Rogers1, Raphael D Isokpehi1,21RCMI-Center for Environmental Health, College of Science, Engineering and Technology, Jackson State University, Jackson, MS 39217; 2Center for Bioinformatics & Computational Biology, Department of Biology, Jackson State University, PO Box 18540, Jackson MS 39217, USABackground: Arsenic is a ubiquitous environmental toxicant, and abnormalities of the skin are the most common outcomes of long-term, low-dose, chronic arsenic exposure. If the balance between keratinocyte proliferation, differentiation, and death is perturbed, pathologic changes of the epidermis may result, including psoriasis, atopic dermatitis, and certain forms of ichthyosis. Therefore, research investigations using in vitro human epidermal cells could help elucidate cellular and molecular processes in keratinocytes affected by arsenic. Data from such investigations could also provide the basis for developing cosmetic intervention for skin diseases caused by arsenic.Methods: The viability of HaCaT keratinocyte cultures with or without prior exposure to low-dose arsenic trioxide was compared for varying concentrations of arsenic trioxide over a time course of 14 days because in untreated control cultures, approximately 2 weeks is required to complete cell differentiation. Long-term cultures were established by culturing HaCaT cells on collagen IV, and cells were subsequently exposed to 0 parts per million (ppm), 1 ppm, 5 ppm, 7.5 ppm, 10 ppm, and 15 ppm of arsenic trioxide. The percentages of viable cells as well as DNA damage after exposure were determined on Day 2, Day 5, Day 8, and Day 14.Results: Using both statistical and visual analytics approaches for data analysis, we have observed a biphasic response at a 5 ppm dose with cell viability peaking on Day 8 in both chronic and acute exposures. Further, a low dose of 1 ppm arsenic trioxide enhanced HaCaT keratinocyte proliferation, whereas doses above 7.5 ppm inhibited growth.Conclusion: The time course profiling of arsenic trioxide cytotoxicity using long-term HaCaT keratinocyte cultures presents an approach to modeling the human epidermal cellular responses to varying doses of arsenic trioxide treatment or exposure. A low dose of arsenic trioxide appears to aid cell growth but concomitantly disrupts the DNA transcription process.Keywords: arsenic trioxide, chronic exposure, DNA damage, HaCaT, keratinocyte, visual analytics